High-resolution analysis of cis-acting regulatory networks at the α-globin locus. - Hughes, J; Lower, K; Dunham, I; Taylor, S; De Gobbi, M; Sloane-Stanley, J; McGowan, S; Ragoussis, J; Vernimmen, D; Gibbons, R; Higgs, D (2013)
We have combined the circular chromosome conformation capture protocol with high-throughput, genome-wide sequence analysis to characterize the cis-acting regulatory network at a single locus. In contrast to methods which identify large interacting regions (10-1000 kb), the 4C approach provides a comprehensive, high-resolution analysis of a specific locus with the aim of defining, in detail, the cis-regulatory elements controlling a single gene or gene cluster. Using the human α-globin locus as a model, we detected all known local and long-range interactions with this gene cluster. In addition, we identified two interactions with genes located 300 kb (NME4) and 625 kb (FAM173a) from the α-globin cluster.